THE LEADERSHIP DEVELOPMENT IN ACCORDANCE WITH BUDDHADHAMMA OF EXECUTIVE OF TAMBOL ADMINISTRATIVE ORGANIZATION IN PHITSANULOK PROVINCE - พระครูสังฆรักษ์เกียรติศักดิ์ กิตฺติปญฺโญ ดอนล่าร์ เสนา,บุญทัน ดอกไธสง (Journal of MCU Social Science Review, 2017)
The study entitled "The Leadership Development In Accordance With Buddhadhamma of executive of Tambol administrative organization in Phitsanulok Province." The objectives of the research were 1. To study the principles of Buddhism that are consistent with the leadership development of Tambol administrative organizations in Phitsanulok Province. 2. To study the leadership of Tambol administration executives In Phitsanulok Province 3. To present The Leadership Development In Accordance With Buddhadhamma of executive of Tambol administrative organization in Phitsanulok Province. The Research is a Mixed Methods Research. Qualitative Research, The researcher collected data from in-depth interviews from 18 informant interviewees who were involved in the Tambol administration organization. Organization Management Or knowledgeable about the organization Academics in higher education institutions And Buddhist experts. And quantitative research The 345 questionnaires were used as a tool for data collection. Qualitative analysis uses descriptive statistics. And quantitative data analysis Use computer programmed social science. To find the frequency, Percentage, mean, standard deviation , and methods for Leadership Development In Accordance With Buddhadhamma of executive of Tambol administrative organization in Phitsanulok province on qualitative and quantitative research. The research found that : The principles of Buddhism that lead to leadership development are (1) the dominance of leadership, namely, the triple digits, the level of leadership development at a high level. (2) the dominion of the four principles of leadership development (3) administrations principle. Leadership development is In a high level. And Personnel working in the Tambol Administration Organization In the Phitsanulok province, The numbers of sampling are 345, The administrators had the level of leadership development in accordance with Buddhadamma of the administrators of Tambol administrative organizations in Phitsanulok Province. The overall level Mean is 4.02 (= 4.02, S.D. = 0.53). The administrators of Tambol administrative organizations in Phitsanulok Province Should have vision management; can apply the Buddhist principles for administration. The overall principle of leadership is the development of self-control. Have a conscious self all the time. Concentrate Is a good man with ethics Honesty Can be exemplary. To present The Leadership Development In Accordance With Buddhadhamma of executive of Tambol administrative organization in Phitsanulok Province found that : Leadership Development Method based on Buddhadhamma. There are 8 ways to develop leadership : Training and practice, Learning, Mentoring, Assignment, Simulation Scenarios, Network Creation, Teaching Tasks , and Model.